Comparison of endoscopic breast-conserving surgery versus conventional breast-conserving surgery for the treatment of early-stage breast cancer: a meta-analysis - Li, Liwen; Liang, Yiwen; Li, Chunyan; Huang, Miaoyan; Liang, Weiming; Qin, Tian (Frontiers in Oncology, 2024)
Introduction This meta-analysis seeks to evaluate the efficacy and safety of endoscopic breast-conserving surgery (E-BCS) compared to conventional breast cancer surgery (C-BCS) in patients diagnosed with early-stage breast cancer. Materials and methods Four databases (Medline, Embase, Web of Science and CENTRAL) were searched published from establishment of database to January 30,2024, for articles studying E-BCS compared to C-BCS in patients diagnosed with early-stage breast cancer. Meta-analyses of procedure time, blood loss, length of incision, drainage duration, total postoperative drainage volume, average duration of hospital stay, positive rate of margin, complication rate, recurrence rate, metastasis rate and cosmetic scoring were performed. Results Totally 11 studies were included for meta-analysis. Compared with C-BCS, E-BCS exhibited significantly reduced incision length (WMD = -6.44, 95%CI: -10.78 to -2.11, P=0.004, I2 = 99.0%) and superior cosmetic scoring (WMD = 2.69, 95%CI: 1.46 to 3.93, P=0.001, I2 = 93.2%), but had significantly longer operation time (WMD = 34.22, 95%CI: 20.89 47.55, P=0.000, I2 = 90.7%) and blood loss (WMD = 3.65, 95%CI: -3.12 to 10.43, P=0.291, I2 = 86.8%). There was no significant difference in terms of recurrence rate, metastasis rate, positive rate of tumor resection margins, drainage duration, drainage volume, complication rate and hospital days. Conclusions Our research findings indicate that E-BCS is a viable and secure method for treating breast cancer in its early stages. E-BCS provides distinct advantages in terms of the length of the incision and the aesthetic result, without demonstrating an elevated recurrence rate or metastasis rate. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024535164, identifier CRD42024535164.